Varied perspectives on play and learning : theory and research on early years education - Lillemyr, Ole Fredrik; Dockett, Sue; Perry, Bob (Emerald Publishing Limited : Information Age Pub., 2013)
This book brings together an international group of researchers reporting on their work about play and early childhood education across 13 countries - Norway, Sweden, Denmark, England, Germany, Hong Kong, United States of America, India, The Maldives, Sri Lanka, Singapore, China and Australia. It contributes to growing international conversations about play and the role of play in early childhood education.Each of the chapters in this anthology reflects different directions in research as well as a range of approaches to reconceptualising play. Each researcher questions assumptions underpinning young children's play and early childhood education and explores the implications of these questions for further research, practice and policy. Chapters report a wide range of innovative and transformative research, focusing on areas such as the play of infants and toddlers, the role of values in play, the complexity of connections between play and learning, motivation, the role and understandings of early childhood educators in promoting children's play, risky play and the impact of Westernised approaches to play in different contexts.This book argues for the importance of children's play at a time when there is a great deal of pressure to increase the academic focus of early education and to eliminate play that could be deemed risky. Several authors note moves towards pedagogies of play and explore the potential links between play and learning in early education settings. The research reported in this book is a timely reminder of the value of play, for and of itself, as well as the learning potential of play. It provides a pathway into the debates about the role and value of play in early years education for students, researchers and policy-makers.